Revitalization of Indonesian criminal law through the acknowledgment of living law: An investigation of the Sigajang Laleng Lipa’ customary law - Harefa, Beniharmoni; Fernando, Zico Junius; Maharani, Asari Suci; Anditya, Ariesta Wibisono; Humana, Sri (Universitas Ahmad Dahlan, 2024)
Introduction to the Problem: The research article examines the Sigajang Laleng Lipa’ tradition in South Sulawesi’s Bugis community as a